A genotype-phenotype study of hereditary multiple exostoses in forty-six Chinese patients - Yuchan Li; Jian Wang; Zhigang Wang; Jingyan Tang; Tingting Yu (BMC, 2017)
Abstract Background Hereditary multiple exostoses (HME) is a rare autosomal dominant skeletal disorder that can cause a variety of clinical manifestations. We aimed to evaluate the general clinical phenotypic severity of HME by using a scoring system and correlate the genotypes with different clinical phenotypes in Chinese patients. Methods Forty-six patients from different families were prospectively enrolled. The mutations were identified by direct sequencing of PCR-amplified genomic DNA or by multiplex ligation-dependent probe amplification (MLPA). Patients' demographic data, height, age of onset, number of anatomical sites, forearm deformity, and lower extremity alignment were analysed according to genotype and gender. A scoring system was used to assess the severity of the clinical phenotype. Results Thirty (60%) patients presented mutations in the EXT1 gene, and 16 (32%) presented mutations in the EXT2 gene. The mean age of onset was 2.96 years. The mean number of involved anatomic sites was 15.35. Male patients had more lesion sites than female patients (15.97 vs. 13.77, p = 0.046). The height evaluation illustrated that 67% of the patients (31 of 46) were below the 50th percentile, and the patients with EXT1 mutations were shorter than those with EXT2 mutations (p = 0.005). Forearm deformity showed a significant correlation with the number of involved anatomical sites (r = 0.382, p = 0.009). Moreover, a higher total score was found in patients with EXT1 mutations (p = 0.001). Conclusions The clinical manifestations of 46 Chinese HME patients were similar to those in previous reports of Western populations. Patients with EXT1 mutations have a more severe clinical phenotype than patients with EXT2 mutations.